Blurring Borders: A Breakdown of China's One-Child Policy and International Adoption Between the United States and China - Tan, Katherine (Colloquium: The Political Science Journal of Boston College, 2025)
Since 1992, China has opened its doors to international adoption. In just 32 years, over 160,000 children have been adopted by families from countries worldwide. Yet, in September 2024, the country announced that it would be halting foreign adoption work, the only exception being "the adoption of a child or stepchild of blood relatives of the same generation who are within three generations of foreigners coming to china to adopt." According to records from the U.S. Department of State, the U.S. has been the largest receiving country of Chinese adoptees. This paper will first explore the history of Chinese domestic policy, which has resulted in a consistently high number of adoptions from China to the U.S., including the role of Malthusian theories, family planning campaigns in the 1970s, and the one-child policy. Then, the focus will shift towards the implications of China's recent decision to stop foreign adoption work on U.S.-China relations. Specifically, the second section will explore how the process of intercountry adoption has produced an unforeseen connection between the U.S. and China, and the consequences of terminating that connection. It will demonstrate how the connection between these countries began with individuals and gradually trickled up to leaders at the national level, ultimately softening the reputations of the U.S. and China to each other's citizens.